PROPOSED BUSINESS STRATEGY IN PALM OIL PLANTATION: CASE STUDY OF PT. XYZ (The Indonesian Journal of Business Administration, 2019)
PT. XYZ is a private palm oil plantation company that produces fresh fruit bunches (FFB) that are sold to palm oil mills. The firm has suffered from declining margin rate that can potentially threaten its sustainable profitability. In order to find prospective solutions, this study conducts analysis based on on internal and external environment scanning method. The external environment analysis consists of PESTLE Analysis, Porter’s Five Forces, and Competitor Analysis. Internal environmental analysis consists of Resources-based View Analysis that composed of examining resources, capabilities, core competencies, value chain analysis, and competitive advantage. The result of both internal and external analysis will be concluded in root cause diagram. Based on the diagram, SWOT Analysis and Internal External Matrix will be used to formulate external and internal strategies. The internal strategies will be derived into business level – based on Porter’s Generic Strategy - and functional level. The research is based on primary data of PT. XYZ and secondary data from publications, press release, and academic journals. The external analysis finds that highly competitive vegetable oil market, weakening demand for palm oil, escalating trade barriers on import, along with surging domestic palm oil production lead to the declining crude palm oil (CPO) in Indonesia. Additionally, in recent years, several new strict regulations imposed by Indonesian government on domestic palm oil industry can potentially restrain future development and expansion. The internal analysis finds that PT. XYZ has competencies in having sufficient number of skilled and experienced field workers, and strong collaboration between Research & Development and field workers. These competencies are appraised as competitive parity and temporary competitive advantage effect respectively. In addition to competencies, operations in PT. XYZ are still considered inefficient. Some of the weaknesses in PT. XYZ that contribute to the inefficiency are labor-intensive culture, cost disadvantage due to scattered estate, manual labor system in harvesting and plant maintenance operations, potentially declining production, and unintegrated and manual management information system. In brief, the root cause of business issue in PT. XYZ in external factor are declining fresh fruit bunch (FFB) price and reduced FFB procurement by palm oil mills. In internal factors, the root cause are increasing labor cost, declining and fluctuating plant production or yield, and increasing general, sales and administration costs. In conclusion, this study proposes business strategy to PT. XYZ to adopt cost leadership, which comprises of highly cost-efficient production process while offering differentiated fresh fruit bunches products to palm oil mills as buyers. This proposed strategy can potentially result in sustainable margin and profitability with sustainable competitive advantage in the long term for PT. XYZKeywords:  Business strategy,  Cost leadership, Marketing, Palm oil, Plantation